The role of the University of the Philippines Elementary School in teacher education - Abdul Azeez Ahamed Jiffri 1917- (1967)
The present investigation of the study is on the role of the U.P. Elementary School in the training of elementary school teachers. Observation, interviews, and literary materials were used to gather data. Results showed that the U.P. Elementary School is an exemplary institution in school and staff organization, professional growth, curricular areas, instructional improvement, evaluation and measurement, pupil personnel services, child growth and development, teaching, class management, materials and resources, student activities, parent-teacher relations and other activities relevant to teacher education.